On the spectrum of the generalized Gelfand pair $(u(p,q), h_{n})$, $p+q=n$ - Godoy, Tomás; Saal, Linda (Mathematica Scandinavica, 2009)
It is known that the spectrum of the Gelfand pair $(U(n), H_{n})$ is homeomorphic to the Heisenberg fan. In this paper after defining a suitable notion of spectrum, we prove an analogous result for the generalized Gelfand pair $(U(p,q), H_{n})$, $p+q=n$.